Theory of constraints: A state-of-art review - Maryam Orouji (Accounting, 2015)
The theory of constraints (TOC) is a management tool, which considers any manageable system as being limited in reaching more of its objectives by some constraints. According to TOC, there is always, at least, one single constraint, and TOC implements a concentrating process to detect the constraint and restructure the remaining of the organization around it. This paper presents an overview of different perspectives of TOC and its implementation in different industries such as project management, quality management, outsourcing, product mix, make-to-buy, accounting, banking and health care, etc. The results indicate that the method has been extensively implemented in different areas of accounting.